Lactobacillus helveticus EL2006H cell-free supernatant enhances growth variables in Zea mays (maize), Glycine max L. Merill (soybean) and Solanum tuberosum (potato) exposed to NaCl stress - Naamala, Judith; Msimbira, Levini A.; Subramanian, Sowmyalakshmi; Smith, Donald L. (Frontiers in Microbiology, 2023)
Plant growth promoting microorganisms and their derived compounds, such as cell-free supernatant, enhance plant growth under stressed and non stressed conditions. Such technology is sustainable and environmentally friendly, which is desirable amidst the climate change threat. The current study evaluated the effect of cell-free supernatant (CFS) obtained from Lactobacillus helveticus EL2006H on its ability to enhance mean percentage germination and mean radicle length of corn and soybean, as well as growth parameters of potato, using treatment formulations that consisted of 0.2 % and 1.0 % [v/v] L. helveticus EL2006H CFS concentrations and 100 mM NaCl and 150 mM NaCl levels. Results show that treatment with 100 mM NaCl lowered percentage germination of corn by 52.63 %, at 72 h, and soybean by 50 %, at 48 h. Treatment with 100 NaCl + 0.2 % EL2006H enhanced percentage germination of soybean by 44.37 %, at 48 h, in comparison to that of the 100 mM NaCl control. One hundred mM NaCl lowered radicle length of corn and soybean by 38.58 and 36.43 %, respectively. Treatment with 100 Mm NaCl + 1.0 % EL2006H significantly increased radicle length of corn by 23.04 %. Treatment with 100 mM NaCl + 0.2 % EL2006H significantly increased photosynthetic rate, leaf greenness and fresh weight of potato. Increasing NaCl concentration to 150 NaCl lowered the effectiveness of the 0.2 % EL2006H CFS on the same growth variables of potato. In general, the lower CFS concentration of 0.2 % was more efficient at enhancing germination in soybean while the higher concentration of 1.0 % was more efficient at enhancing radicle length of corn. There was an observed variation in the effectiveness of L. helveticus EL2006H CFS across the different CFS concentrations, NaCl levels and crop species studied. In conclusion, based on findings of this study, CFS obtained from L. helveticus can be used as a bio stimulant to enhance growth of corn, soybean and potato. However, further studies need to be conducted, for validation, especially under field conditions, for commercial application.